The effects of a peaking protocol on heart rate variability and its predictive associations with wilks coefficient in competitive powerlifters - Cholewinski, M.; Machek, S.; Cardaci, T.; Wilburn, D.; Willoughby, D.; Funderburk, L.; Gallucci, A. (International Journal of Strength and Conditioning, 2022)
Powerlifting competition is comprised of three barbell lifts: squat, bench press, and deadlift that are all completed in a single day and summed together, ultimately normalized to the lifter`s body weight via the Wilks Coefficient. This figure is then subsequently employed to determine the "best" athlete in that meet. During the competition preparation, powerlifters often undergo peaking protocols which include physiologically taxing overreach and low-volume, recovery-focused taper phases to collectively induce super-compensatory strength adaptations. Heart rate variability (HRV) has emerged as an easily accessible, user-friendly biomarker for autonomic nervous system-associated fatigue and readiness. Therefore, the purpose of this observational study was to investigate the potential impact of a peaking protocol on fatigue/readiness via HRV measurements and its possible relationship with competitive powerlifting performance. Daily measurements of HRV were taken, each morning, using the HRV4Trainning smartphone application by nineteen competitive powerlifters (26.16±4.56 years) from 14-days prior to a peaking protocol, throughout individual peaking phases, on meet day, and 14-days following competition. A quadratic regression was used to determine the predictability of HRV measurements and powerlifting performance. The change in HRV from competition day to baseline was found to be a significant predictor of Wilks coefficient (p=0.038,